Websites Most Frequently Used by Physician for Gathering Medical Information - De Leo, G. (American Medical Informatics Association, 2006)
Physicians’ use of the Internet to gather medical information has increased in recent years. Several studies have been conducted to explore the implications of this use on patient education, the physician-patient relationship, and diagnosis/decision making. In order to better understand the current and future implications of Internet use on patient care activities, it is important to know the Internet sources physicians prefer to consult. The objective of this study was to determine the Internet sources of information physicians most often use to gather medical information. This study demonstrated that the vast majority of physicians indicate they access a targeted site rather than utilize a search engine (such as Google©) to gather medical information. Of the targeted site types, most physicians indicate they use 1) edited/secondary data sources as their primary medical information data retrieving, 2) about one quarter of the physicians surveyed indicated research databases which provide access to medical journal publications 3) a minority of physicians use sites dedicated to their specialized area and 4) a small percentage use medical web site portals.